Fabrication of PLA/CNC/CNT conductive composites for high electromagnetic interference shielding based on Pickering emulsions method. (October 2019) - Yu, Bowen; Zhao, Zhiyu; Fu, Sirui; Meng, Lu; Liu, Yuhang; Chen, Feng; Wang, Ke; Fu, Qiang
Abstract: In this study, we proposed a new strategy to fabricate polylactide (PLA) based conductive polymer composites with excellent electrical conductivity, superior electromagnetic interference shielding efficiency (EMI SE) and good mechanical properties using a Pickering emulsions method. Cellulose nanocrystals (CNCs) were used as a stabilizer for oil-in-water Pickering emulsions and a dispersant for carbon nanotubes (CNTs) at the same time. CNC/CNT suspensions and dichloromethane (DCM) solution of PLA were used as aqueous phase and oil phase respectively. With the evaporation of DCM, PLA microparticles coated by entangled CNCs and CNTs could be formed. After compression molding, the PLA/CNC/CNT composites showed an outstanding EMI SE of 41.8 dB with only 4.3 wt% CNT loading. Simultaneously, the mechanical performance of the sample maintained a high level (tensile strength: 45.52 MPa, Young's Modulus: 3152 MPa). Our findings provide a simple, cost-effective and environmentally friendly manufacturing route for functional polymer nanocomposites with excellent comprehensive properties.